Emergency endotracheal intubation in critically ill patients with COVID-19: management and clinical characteristics - Fang, Fuquan; Jin, Jing; Pi, Yongmin; Guo, Shaohui; Li, Yuhong; Zhu, Shengmei; Kang, Xianhui (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2023)
Purposes SARS-CoV-2 have become widespread worldwide since the outbreak. Respiratory function deteriorates rapidly in critically ill patients infected with SARS-CoV-2. Endotracheal intubation is an indispensable therapeutic measure during the development of the disease. This study was intended to describe the experience of endotracheal intubation from front-line anesthesiologists and clinical prognosis of patients infected with Coronavirus disease-19 (COVID-19). Methods Fourteen critical patients infected with COVID-19 who underwent endotracheal intubation were included in this study. We collate and analyze the blood gas results before and after tracheal intubation of patients and clinical prognostic indicators such as length of stay and. mortality. The experience of anesthesiologists who intubated patients has also been recorded in detail. Results Patients had a mean time of 10.6 days from initial symptoms to endotracheal intubation. Most intubated patients had one or more underlying conditions: hypertension (8, 57.14%), diabetes (5, 35.71%), and cardiovascular and cerebrovascular diseases (2, 14.29%). The oxygenation index increased significantly after intubation compared with before intubation (148.80 ± 42.25 vs 284.43 ± 60.17 p < 0.001). 85.72% of patients required extra-corporeal membrane oxygenation (ECMO) due to inability to maintain oxygen saturation with standard therapeutic measures. Two patients underwent lung transplantation because their lungs were essentially nonfunctional, and they recovered well after surgery. As of this writing, all patients were discharged after satisfactory recovery. Conclusions Reasonable selection of intubation timing is particularly important. It is crucial to increase the patient's oxygen supply and reduce oxygen consumption as much as possible during endotracheal intubation. In addition, the personal protective measures of medical personnel participating in treatment should be scientific and standardized. Graphical Abstract